Comparative Analysis of Two Helicobacter pylori Strains using Genomics and Mass Spectrometry-Based Proteomics - Karlsson, Roger; Thorell, Kaisa; Hosseini, Shaghayegh; Kenny, Diarmuid; Sihlbom, Carina; Sjöling, Åsa; Karlsson, Anders; Nookaew, Intawat (Frontiers in Microbiology, 2016)
Helicobacter pylori, a gastroenteric pathogen believed to have co-evolved with humans over 100,000 years, shows significant genetic variability. This motivates the study of different H. pylori strains and the diseases they cause in order to identify determinants for disease evolution. In this study, we used proteomics tools to compare two H. pylori strains. Nic25_A was isolated in Nicaragua from a patient with intestinal metaplasia, and P12 was isolated in Europe from a patient with duodenal ulcers. Differences in the abundance of surface proteins between the two strains were determined with two mass spectrometry-based methods, label-free quantification (MaxQuant) or the use of tandem mass tags (TMT). Each approach used a lipid-based protein immobilization (LPI™) technique to enrich peptides of surface proteins. Using the MaxQuant software, we found 52 proteins that differed significantly in abundance between the two strains (up- or downregulated by a factor of 1.5); with TMT, we found 18 proteins that differed in abundance between the strains. Strain P12 had a higher abundance of proteins encoded by the cag pathogenicity island, while levels of the acid response regulator ArsR and its regulatory targets (KatA, AmiE, and proteins involved in urease production) were higher in strain Nic25_A. Our results show that differences in protein abundance between H. pylori strains can be detected with proteomic approaches; this could have important implications for the study of disease progression.